(untitled) (Libellarium: journal for research in the field of information and related sciences, 2015)
In order to remain relevant in society, archivists should promote collections and records that are kept in the archives. Through public programmes, archives interact with customers and various public actors and create the institutional image. This paper is concerned with the role of public programmes in the process of modernization of the archival practice, with the emphasis on the Croatian state archives. The aim of the paper is to identify what kind of information is offered to users and public in general on the web sites of the Croatian state archives. Public programmes involve two important components of archival practice: archives and users. Therefore, public programmes ensure good relations with the public. Croatian archivists still question the need for public relations in archives, while American and European archives have already integrated public relations into the basic archival functions. The key components needed for successful planning and implementation of public programs are the source of financing, compliance with the annual work plan, clear goals, defined target audience, cooperation and support from the local community, and the evaluation of results.